2023
DOI: 10.1002/ece3.10828
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the phylogenetic relationship among varieties of Toona ciliata (Meliaceae) in sympatry with chloroplast genomes

Yu Xiao,
Xi Wang,
Zi‐Han He
et al.

Abstract: Toona ciliata is an endangered species due to over‐cutting and low natural regeneration in China. Its genetic conservation is of an increasing concern. However, several varieties are recognized according to the leaf and flower traits, which complicates genetic conservation of T. ciliata. Here, we sequenced the whole chloroplast genome sequences of three samples for each of four varieties (T. ciliata var. ciliata, T. ciliata var. yunnanensis, T. ciliata var. pubescens, and T. ciliata var. henryi) in sympatry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 108 publications
(122 reference statements)
1
4
0
Order By: Relevance
“…Information on well-mixed genetic relationships among all samples derived from phylogenetic relationships (Figures 5 and 6) is partially consistent with the results of four varieties assayed with chloroplast sequences [21]. This supports the previous recommendation of conserving the genetic variation of this species in terms of the T. ciliata complex rather than individual varieties.…”
Section: Genetic Conservationsupporting
confidence: 88%
See 3 more Smart Citations
“…Information on well-mixed genetic relationships among all samples derived from phylogenetic relationships (Figures 5 and 6) is partially consistent with the results of four varieties assayed with chloroplast sequences [21]. This supports the previous recommendation of conserving the genetic variation of this species in terms of the T. ciliata complex rather than individual varieties.…”
Section: Genetic Conservationsupporting
confidence: 88%
“…The distribution of haplotypes in the western region was consistent with previous results. Xiao et al [ 21 ] showed well-mixed phylogenetic relationships among individuals of four varieties of T. ciliata in Yunnan Province ( T. ciliata var. ciliata , T. ciliata var.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its genetic conservation is of increasing concern due to overcutting and a low natural regeneration rate in China. A conservation strategy based on the T. ciliata complex rather than a single variety was recommended from the analysis of the population genetic structure [3] and phylogenetic relationships among varieties [45]. A similar case was also reported in an endangered Araucaria angustifolia, whose varieties were rarely considered in conservation strategies [46,47].…”
Section: Limitations Of Species-based Genetic Conservationmentioning
confidence: 89%